ZrTiO4 Nanowire Growth Using Membrane-assisted Pechini Route - de Lucena, Poty Rodrigues; Prado, Willian Andrade; Braga, Valdeilson Souza; Carreño, Neftali Lenin Villarreal (Orbital: The Electronic Journal of Chemistry, 2016)
The high surface-to-volume ratio of nanowires makes them natural competitors as newer device components. In this regard, a current major challenge is to produce quasi-one-dimensional nanostructures composed of well-established oxide-based materials. This article reports the synthesis of ZrTiO4 nanowires on a silicon (100) wafer in a single-step deposition/thermal treatment. The template-directed membrane synthesis strategy was associated with the Pechini route and spin-coating deposition technique. ZrTiO4 nanowires were obtained at 700 °C with diameters in the range of 80-100 nm. FEGSEM images were obtained to investigate ZrTiO4 nanowire formation on the silicon surface and energy dispersive X-ray detection (EDS) and X-ray diffraction (XRD) analyses were performed to confirm the oxide composition and structure. DOI: http://dx.doi.org/10.17807/orbital.v1i1.711